Effects of heat stress on growth performance, carcass traits, serum metabolism, and intestinal microflora of meat rabbits - Liu, Hongli; Zhang, Bin; Li, Fan; Liu, Lei; Yang, Tongao; Zhang, Haihua; Li, Fuchang (Frontiers in Microbiology, 2022)
To investigate the effects of heat stress on meat rabbits, we assigned 80 rabbits to the moderate temperature group (24 ± 1°C; Control group) and the continuous high-temperature group (HT group), then monitored the effects using growth performance, carcass characteristics, biochemical assays, UPLC–MS/MS-based metabolomics, and microbiome. The results showed that after continuous high-temperature exposure, the average daily gain, average daily feed intake, and thymus index were significantly decreased (p < 0.05). Contents of HSP70, ALP, and Cortisol in serum were significantly increased, while TP, GLU, T3, and T4 were significantly decreased (p < 0.05). Nine kinds of differential metabolites were screened by serum metabolomics, which can be used as biomarkers of heat stress in meat rabbits. The selected differential metabolites were analyzed by KEGG annotation and enrichment analysis. The results showed that 14 pathways affected by heat stress were identified by KEGG pathway enrichment analysis, including Sphingolipid metabolism, Pyrimidine metabolism, Citrate cycle (TCA cycle)), aminoacyl-tRNA biosynthesis, and so on. The analysis of the effect of heat stress on the cecal microflora of meat rabbits showed that the abundance of cecal Proteus in the HT group was significantly higher than that in the moderate Control group. The number of Candidatus-saccharimonas in the cecum microflora was significantly higher than that in the moderate temperature group (p < 0.05) which may be related to inflammatory diseases in the heat stress group. These findings indicated that the heat-stressed rabbits were in negative energy balance, which affected protein metabolism, and subsequently affected growth performance and carcass characteristics.